TEACHING READING COMPREHENSION BY USING LISTEN-READ-DISCUSS (LRD) STRATEGY TO THE TENTH GRADE STUDENTS OF SMK YADIKA LUBUKLINGGAU - nova sintia (Journal of English Education, Literature and Linguistics, 2020)
The objective of this study was to find out whether or not it is effective to teach reading comprehension by using comprehension Listen-Read-Discuss (LRD) Strategy to the Tenth Grade Students of SMK Yadika Lubuklinggau in academic year 2019/2020. The writer formulated two hypotheseses in this study. There were null hypotheses (Ho) and the alternative hypotheses (Ha). The population of this study was all the tenth grade students at SMK Yadika Lubuklinggau in academic year 2019/2020 and the total of the sample was 34 students. The sample of this study was taken through purposive sampling technique. The writer used the pre-experiment method. The collecting of data, the writer used the written test that was given twice to students. The first, the writer gave pre-test. The second, the writer gave post-test in analyzing the data, the writer used three techniques: individual score, conversion score, and hypotheses testing. Based on the result of analyzing the data, the writer found that the average of students in pre-test was 62.35. On the other hand, in the post-test their average score increased to be 76.47. The result of matched test was 6.75, while t-table was 1.692 (Ha) was accepted. So It meant that it was significantly effective to teach reading comprehension by using comprehension Listen-Read-Discuss (LRD) Strategy to the Tenth Grade Students of SMK Yadika Lubuklinggau in the academic year 2019/2020.